The islamic epistemological element of Al-Yaqin in critical thinking - Endut, M.N.A.-A. (Universiti Putra Malaysia, 2015)
To think, in Islam, is actually to perform an act of worship ('ibadah) and it is the thinking that strongly induces one's belief, faith and personality. The failure to engage critical thinking with Islamic Worldview could expose Muslim students to the misconception of the thinking as to perceive it peculiar from the Islamic teaching. This paper aims to explore and reveal the epistemological concept of al-yaqin as part of the Islamic essential elements of critical thinking. Library research method is employed in addressing the issues of critical thinking from the Islamic perspective, where Muslim prominent classical works were reviewed and analysed inductively in order to come out with essential Islamic epistemological elements of critical thinking. The exposition of the concept is illustrated from the theoretical and methodological context al-yaqin and its implicit relation to critical thinking. The study signifies two edges of epistemological nature of critical thinking; from the data verification process to the conclusion state of a belief, which distinguish firm factual knowledge from vague assumptions. The findings of this paper distinguish critical thinking from the Islamic worldview to be advocated among Muslim students as an alternative to the existing modern concept of critical thinking. Â© Universiti Putra Malaysia Press.